MARRIAGE IN DIFFERENT RELIGIONS: BETWEEN TEXT AND CONTEXT - Khairul Hamim (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
The rapid development of the era, marked by the advancement of science and technology, has given ample scope for the creation of a very dynamic plural society. Inter-human interaction, whether religious or non-religious, is unavoidable, including marriage. Many people in the modern world are currently married to unbelievers. This phenomenon often raises questions in the community about whether or not someone can marry someone with different faith (religion)? For this reason, this paper seeks to provide answers by expressing various explanations and opinions from scholars.